Small but beautiful? Economic impacts of the size of nations in the European Union - Jörg König; Renate Ohr (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2011)
This paper highlights the economic meaning of the size of the state for members of the European Union, thereby making the economic success of EU states statistically tangible. Firstly, we show in descriptive illustrations that the theoretically expected characteristics of small countries clearly apply to the current EU states. From the theoretical perspective, only the bivariate relationship between the population size and the economic growth initially depicts an unexpected sign. However, the econometric analysis performed on our panel data set confirms the assumption that this relationship is strongly influenced by factors other than population size, such as the duration of EU membership, the level of economic development (transformation process) and the increased development potential provided by EU funds. When subtracting these effects through appropriate statistical methods, there is an overall significant positive dependence of economic growth on the size of the state.
Keywords: C23; F15; F43; O52; 330; European Union; economic integration; small open economy; size of nations; economic growth; panel data.; Landesgröße; Wirtschaftswachstum; Kleines-offenes-Land; Wirtschaftsintegration; Panel; Schätzung; EU-Staaten